A Rare Culprit or an Elusive Culprit in Disguise? Unraveling Wild-Type ATTR Cardiac Amyloidosis in Heart Failure With Reduced Ejection Fraction - Jose Loayza Pintado MD; Taiwo Ajani MD; Daniela Hernandez MD; Everardo Cobos MD (Journal of Investigative Medicine High Impact Case Reports)
Cardiac amyloidosis (CA) is a rare disorder caused by the deposition of abnormal proteins called amyloid in the myocardium, leading to dysfunction. The 2 most common forms of amyloidosis are AL (light chain) and ATTR (transthyretin). Diagnosing amyloidosis is challenging, especially in its early stages, due to its nonspecific symptoms and overlap with other conditions. Recent studies suggest that the incidence of wild-type transthyretin amyloidosis is rising, likely due to improved diagnostic techniques and an aging population. We present the case of a 72-year-old male with lower extremity edema, progressive shortness of breath, and worsening renal function. He had a significant medical history, including hypertension, small lymphocytic lymphoma, coronary artery disease, diabetes, and chronic kidney disease. Physical examination revealed orthostatic hypotension and peripheral neuropathy. Imaging showed restrictive cardiomyopathy with reduced ejection fraction. Laboratory tests confirmed anemia and proteinuria, while a bone marrow biopsy ruled out AL amyloidosis. A Tc-99m pyrophosphate scan confirmed the diagnosis of ATTR CA. ATTR often presents with multi-organ involvement, complicating diagnosis. This patient’s coexisting conditions, including orthostatic hypotension and renal failure, may have been aggravated by amyloidosis. Misdiagnosis between AL and ATTR can lead to inappropriate treatments, making accurate diagnosis crucial. ATTR requires transthyretin stabilizers and symptom management, while AL needs chemotherapy. Treatment of amyloidosis must be individualized, as autonomic dysfunction, arrhythmias, and renal involvement require careful management. Early diagnosis and differentiation are essential for appropriate treatment and improved outcomes in patients with multi-organ involvement.